Optimization of the determination of volatile organic compounds in plant tissue and soil samples: Untargeted metabolomics of main active compounds - Nipapan Kanjana; Muhammad Afaq Ahmed; Zhongjian Shen; Yuyan Li; Lisheng Zhang (MethodsX, 2024)
This review critically assesses the determination of low molecular weight volatiles by different methods, providing context for the development of suitable techniques to determine volatile content in plant tissue and soil samples as well as the associated analytical challenges. Although sensitive analytical methods have been reported in recent decades, studies on their application in modern investigative techniques are lacking. Herein, the latest sampling methods in volatile biochemistry, current advancements in the understanding of these analytes, and the significance of these findings for other types of volatiles are summarized. Gas chromatography, high-performance liquid chromatography, ion chromatography, thin-film microextraction, and real-time monitoring techniques are discussed and critically determined. This review concerns the methods most suitable for future research in this area.